2020
DOI: 10.21203/rs.3.rs-18686/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modified FOLFIRINOX as a second-line therapy following gemcitabine plus nab-paclitaxel therapy in metastatic pancreatic cancer

Abstract: Purpose There is no established second-line treatment after failure of gemcitabine plus nab-paclitaxel (GnP) therapy for metastatic pancreatic cancer (MPC). This study aimed to evaluate the efficacy and tolerability of the modified FOLFIRINOX (mFFX) as a second-line therapy for MPC and investigate prognostic factors for survival.Methods From 2015–2019, we retrospectively reviewed the medical records of patients receiving mFFX for MPC after failure of GnP therapy. Patients were treated every 2 weeks with mFFX (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
2
13
2
Order By: Relevance
“…In the phase III ACCORD11 trial, the efficacy of FOLFIRINOX as a first‐line treatment was superior to that of GEM, 5 although the trial revealed several safety concerns, such as febrile neutropenia and anorexia. The efficacy and safety of mFOLFIRINOX as a first‐line treatment have been demonstrated 6,24 and those of mFOLFIRINOX as a second‐line treatment have been reported; the reported median OS with mFOLFIRINOX as a second‐line treatment ranges from 7.0 to 10.3 months 18–20 . In our study, the median OS of 10.6 months in the mFOLFIRINOX group was not inferior to that reported in previous studies, although this is a comparison between different trials and requires careful consideration.…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…In the phase III ACCORD11 trial, the efficacy of FOLFIRINOX as a first‐line treatment was superior to that of GEM, 5 although the trial revealed several safety concerns, such as febrile neutropenia and anorexia. The efficacy and safety of mFOLFIRINOX as a first‐line treatment have been demonstrated 6,24 and those of mFOLFIRINOX as a second‐line treatment have been reported; the reported median OS with mFOLFIRINOX as a second‐line treatment ranges from 7.0 to 10.3 months 18–20 . In our study, the median OS of 10.6 months in the mFOLFIRINOX group was not inferior to that reported in previous studies, although this is a comparison between different trials and requires careful consideration.…”
Section: Discussionsupporting
confidence: 39%
“…Although the regulatory approval of nal‐IRI/5‐FU/LV has clarified the principle of treatment, the selection of second‐line chemotherapy regimen for unresectable pancreatic cancer is controversial. In such circumstances, several studies have confirmed the efficacy and safety of mFOLFIRINOX as a second‐line treatment; its clinical usefulness as a first‐line treatment has already been established 6,18,19,24 . The consideration of mFOLFIRINOX, the standard first‐line treatment alongside GnP, as a second‐line treatment is natural and reasonable in cases where it has not been used as a first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other second-line therapy options after GA, are FOLFIRINOX/mFOLFIRINOX and FOLFIRI, especially where Nal-IRI is not available. A recently published retrospective study showed, for patients in good performance status (ECOG 0/1) with progressing disease on GA, showed a median OS of 7.0 months under a second-line treatment with mFOLFIRINOX (omission of 5-FU bolus) [ 31 ]. The median OS after the start of first-line therapy was 15.9 months.…”
Section: Mainstay (First Second Line and Biomarker Driven Treatmmentioning
confidence: 99%
“…Real-world studies reported in the literature have included estimates of the prognostic impact of patient and disease characteristics in patients receiving systemic therapy for mPDAC. [17][18][19][20][21] Such studies have been limited in sample size due to a reliance on one or a limited number of study centers or a focus on patients receiving a particular drug regimen. This has limited their usefulness for guiding decision-making in the treatment of patients with mPDAC.…”
Section: Introductionmentioning
confidence: 99%